E-Module Based Health Education on COVID-19 Immunization Increases Public Knowledge - Alfikrie, Fauzan; Hidayat, Uti Rusdian; Akbar, Ali; Arisandi, Defa; Hatmalyakin, Debby; Nurpratiwi, Nurpratiwi; Amaludin, Mimi; Safitri, Dewin (Sarana Ilmu Indonesia (salnesia), 2025)
The Indonesian government has declared COVID-19 as endemic, marking the end of the pandemic phase. However, efforts to control and prevent severe disease continue through routine COVID-19 immunization. Coverage for the second primary dose and booster remains below target. This study aims to evaluate the effect of an e-module on COVID-19 immunization knowledge among residents of Pontianak City. A quasi-experimental design with a control group was used. Forty-four participants were selected through accidental sampling and divided into two groups: 22 in the intervention group (e-module) and 22 in the control group (leaflet). Wilcoxon test results showed both the e-module (p-value = 0,000) and the leaflet (p-value = 0,001) significantly improved participants’ knowledge. The Mann-Whitney test (p-value = 0,039; mean rank = 26,1 vs. 18,8) indicated the e-module was more effective than the leaflet. E-module evaluation was conducted after three days of self-learning. Further studies are recommended to assess long-term knowledge retention and accessibility through digital learning tools on COVID-19 immunization.